Ibn Athaillah's Theodicy Thoughts About Ugliness - Bagus Nurwahyu Akhmad Faridatullah; Radea Yuli Ahmad Hambali; Maman Lukmanul Hakim; Yoshy Hendra Hardiyan Syah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This article discusses ibn Athaillah's philosophical thinking about the ugliness of the covid-19 case study as an implication of ugliness. Theology is a study in which it tends to question the justice and omnipotency of god. The study is based on literature review (Literature Review) in its literature review and in its descriptive and scholarly analysis of ibn Athaillah's corrupt thinking. In this study, the approach referred to is the